INPUT AND OUTPUT TO IMPROVE ENGLISH SPEAKING SKILLS BASED ON YOUTUBE VIDEO LESSONS - Fadilah Fadilah; Fiza Asri Fauziah Habibah (Pujangga: Jurnal Bahasa dan Sastra, 2021)
ABSTRACTThe present study attempts to explore kinds of input and output to improve English speaking skills based on YouTube video lessons. The theory of input was proposed by Krashen, while the output was taken from the output hypothesis of Swain. This study employed qualitative descriptive method, which is a method of research that attempt to describe and interpret the objects in accordance with reality The main instrument was collecting the data, observing the data by watching the whole ten videos, then classifying every tips to two general main paths: input and output. The study showed variety of input which are found on the ten YouTube video lessons are listening that can be achieved by observing in form of listening podcast and listening music in English and learn the lyrics, and varies of reading which are reading Speed reading, Reading aloud to practice pronunciation, Reading a book, blog post, news, Reading children’s book. Kinds of output gained from those videos are speaking which are Talk to yourself, Have a speaking partner, Talk with a native, Using imitation technique, Join a discussion, Speak loudly, Make video, Creative practice, Spend time with people who speak English, and writing which is described more specifically on that video as writing a daily journal.